Technology Applied to ELT: Reviewing Practical Uses to Enhance English Teaching Programs - Javier Rojas Serrano (Asociación Colombiana de Profesores de Ingles, 2007)
In this paper, the author reports on some of the areas of technology currently used in the teaching and learning of languages, and reviews some of the uses of technological tools that are present in the English Adult Program and activities carried out at The Centro Colombo Americano (CCA) in Bogota, Colombia. After briefly describing what is being applied worldwide in terms of what is being done at the CCA, some suggestions are offered in order to enhance the English teaching and learning processes through the use of new technologies.